PERAN SELF TALENT BRANDING DAN ORGANIZATIONAL SUPPORT TERHADAP MINAT BERKARIR DI BUMN MELALUI MEDIASI SELF EFFICACY DAN CAREER ADAPTABILITY - Budiarti, Sari (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
Students’ career interest has become a critical issue in navigating the dynamic and complex challenges of today’s job market. This study aims to analyze the influence of Self-Talent Branding and Organizational Support on students’ Career Interest, both directly and through the mediating variables of Self-Efficacy and Career Adaptability. A quantitative approach was employed using a causal research design and data collected through questionnaires distributed to 150 final-year undergraduate students. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results revealed that both Self-Talent Branding and Organizational Support significantly influence Career Adaptability, which in turn has a positive impact on students’ Career Interest. The mediating pathway from Organizational Support through Career Adaptability to Career Interest was also found to be significant, highlighting the crucial role of career adaptability in linking organizational support and students’ career aspirations. Conversely, Self-Efficacy did not exhibit a significant effect, either directly on Career Interest or as a mediator between Self-Talent Branding and Organizational Support and Career Interest. The study concludes that Career Adaptability is a substantial mediating variable in the relationship between personal branding and organizational support and students’ career interest. Future research is recommended to explore additional factors such as social environment, internship experiences, and future orientation to deepen the understanding of how career interest is developed among young generations